Molecular identification, genetic diversity and distribution of Theileria and Babesia species infecting small ruminants - Altay, Kursat; Dumanli, Nazir; Aktas, Munir (Elsevier Science Bv, 2007)
Detection and identification of Theileria and Babesia species in 920 apparently healthy small ruminants in eastern Turkey, as well as parasite genetic diversity, was investigated using a specifically designed reverse line blot (RLB) assay. The hypervariable V4 region of the 18S ribosomal RNA (rRNA) gene was amplified and hybridized to a membrane onto which catchall and speciesspecific oligonucleotide probes were covalently linked. Three Theileria and one Babesia genotype were identified. Comparison of the Theileria genotypes revealed 93.6-96.2% similarity among their 18S rRNA genes. Two Theileria shared 100% and 99.7% similarity with the previously described sequences of T. ovis and Theileria sp. OT3, respectively. A third Theileria genotype was found to be clearly different from previously described Theileria species. The genotype was provisionally designated as Theileria sp. MK. The Babesia genotype shared 100% similarity with Babesia ovis. The survey indicated a high prevalence of piroplasm infections in small ruminants (38.36%). Theileria spp. prevalence was 36.08%. Prevalence of B. ovis was 5.43%. The most abundant Theileria species identified was T ovis (34.56%) followed by Theileia sp. MK (1.30%) and Theileria sp. OT3 (0.43%). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Theileria; Babesia; PCR; microscopy; sheep; goats